Monitoramento sorológico e da presença do DNA pró-viral do lentivirus caprino (CAEV) no sangue e semen de reprodutores infectados - Juliano Cezar Minardi da Cruz (2009)
Caprine arthritis-encephalitis (CAE) is a multisystemic viral syndrome in goats caused by small ruminant lentivirus (CAEV). The control measures prescribed for CAEV control are based on the indentification of infected animals through a suitable serological test. The aim of this work was to improve the CAE control measures through the association of indirect (agar gel immunodiffusion-AGID) and direct (nested-PCR) assays to CAEV diagnosis. AGID was performed at birth before colostrum, at day of infection and throughout 12 months pos infection. We studied the viral shedding in a group of nine experimental infected males over a year by following the proviral load by nested-PCR in semen and blood. During the experimental period (EP) no clinical signs of CAE were observed. Throughout the EP one animal (1/9) remained AGID-seronegative to CAEV. When the semen samples were submitted to PCR, that same AGID-seronegative animal showed positive results. Delayed seroconversion appears to be a feature of CAEV infection wich may have direct implications for eradication programs and epidemiologic studies that rely on serologic methods to detect infected goats. Our results suggest that the bucks show intermittent shedding of proviral DNA into ejaculated semen. No significant relationship was found between the presence of proviral CAEV DNA in blood and the detection of proviral CAEV DNA in ejaculates. We conclude that the classical management practices recommended for CAEV control are insufficient in CAEV eradication programs and that PCR may be a useful tool for decreasing the risk of breeding AGID false negative animals